CRITICAL ANALYSIS OF THE CLEANLINESS, HEALTH, SAFETY, ENVIRONMENT SUSTAINABILITY (CHSE) CERTIFICATION PROGRAM FOR BUSINESS ACTORS TOURISM AND CREATIVE ECONOMY - Mukhlis, Mukhlis; BS Sukamdani, Hariyadi; Hasibuan, Bernard (Penerbit Lafadz Jaya, 2025)
The COVID-19 pandemic has significantly affected the tourism sector in Indonesia, causing a dramatic decline in the number of tourists. The government responded with the implementation of the CHSE protocol to restore and rebuild trust and tourism activities. The purpose of this research is to investigate the implementation, evaluation, and development strategy of CHSE certification programs in the tourism and creative economy sectors. Research Methodology. The qualitative evaluation research uses the CIPP model to evaluate the implementation of CHSE certification programs in the Indonesian tourism industry, focusing on data collection, analysis, and recommendations for improving program effectiveness in the context of the COVID-19 pandemic. Results and Discussion. An evaluation of the implementation of the CHSE certification program in 120 tourism and creative economy businesses highlights the perception of business leaders on the relevance and implementation of the program and its impact on tourist visits and business income. Conclusions and Suggestions. The implementation of CHSE certification covers more than 12,027 tourism businesses in 403 districts/cities in 34 provinces since 2020. The evaluation recommended changes to mandatory policies to increase their adoption and effectiveness, supported by development strategies including the synergy of tourism business standards, the implementation of SNI 9042, and impact research on consumer decisions.